Effectiveness of Early Intervention Programs for Young Children with Global Developmental Delay: A Systematic Review - Almuhanna, Sarah Mohammed; Alshehri, Omar Ahmed; B. Alsaadoon, Bandar Mohammed; Mohammed Alawad, Mohammed Hassan; Alnasyan, Abdullah Mohammed; Abuabat, Salman Abdullah; Akshay Kiran, Myle (Galen Medical Journal, 2025)
Background: There are many children worldwide who suffer from ECDD and these delays may negatively affect their health, education and integration with others in long-term. Identifying developmental delays at an early stage is sometimes difficult due to the absence of standardized methods, misconceptions and little training in healthcare. Developmental delays must be handled carefully so that they do not cause harm children in the long run. Materials and Methods: The systematic review included 16 articles according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The review included research only on developmental delays happening in the domains of cognitive, language, motor or social-emotional skills. Results: The review looks at the latest findings on the diagnosis, treatment and results connected to ECDD. A pooled meta-analysis of seven studies indicated that children from low-income households had a significantly higher risk of developmental delays, with a combined odds ratio (OR) of 2.38 (95% Confidence Interval [CI]: 1.75–3.22, p < 0.001). Protective factors were also identified; for example, three studies showed that access to early childhood education programs reduced the risk of ECDD, with an OR of 0.61 (95% CI: 0.43–0.86). Conclusion: The study highlights the importance of having policies that focus on early detection and complete care to support children’s healthy development and good quality of life. The review notes that future research should also make it a priority to study how early intervention affects long-term outcome in various kinds of contexts and population.